If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 5 = 12 + 7b Reorder the terms: 5 + 8b = 12 + 7b Solving 5 + 8b = 12 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. 5 + 8b + -7b = 12 + 7b + -7b Combine like terms: 8b + -7b = 1b 5 + 1b = 12 + 7b + -7b Combine like terms: 7b + -7b = 0 5 + 1b = 12 + 0 5 + 1b = 12 Add '-5' to each side of the equation. 5 + -5 + 1b = 12 + -5 Combine like terms: 5 + -5 = 0 0 + 1b = 12 + -5 1b = 12 + -5 Combine like terms: 12 + -5 = 7 1b = 7 Divide each side by '1'. b = 7 Simplifying b = 7
| -4x-1=-7 | | 4(y-4)=8 | | y=3x+4 | | 5x+2=2(x+6) | | 9-30x=-42-27x | | -5x+10=45 | | 5+6=126 | | z+11.2=-6.5 | | 56=112z | | 12x+8-4=11x-3 | | 48=6m | | 1.5x^2-24x-24=0 | | -10=k-11 | | 7=x-9 | | -6+y=-11 | | 15x-5=10x+35 | | 13x-2y=70 | | -6(1-2x)-12=0 | | y=-5x-7 | | 4x+-10=-4x+22 | | 4(2z-4)=-4(z-2) | | 7(3-y)=-3y+5 | | 4x+93=-3x+9 | | 6c=4(c+5) | | -5(6n+2)=20 | | 15.7x-2.7x=-26 | | 6a+3=8a-21 | | 5t+5=5t-4 | | 9=3(3x-3) | | 3x-4y=7 | | 4x=3y+20 | | 23+x=-52 |